A combined chemo-enzymatic treatment for the oxidation of epoxy-based carbon fiber-reinforced polymers (CFRPs) - Wongwattanarat, Sasipa; Schorn, Andrea; Klose, Leon; Carré, Camille; Malvis Romero, Ana; Liese, Andreas; Pérez-García, Pablo; Streit, Wolfgang R. (Frontiers in Bioengineering and Biotechnology, 2025)
Carbon fiber-reinforced polymers (CFRPs), particularly epoxy-based composites, have become essential in the aerospace, automotive, and wind energy industries due to their robust mechanical properties, and lightweight nature. However, there is a lack of recycling technologies that are environmentally sustainable while also ensuring the recovery of carbon fibers in their original state. Although certain bacterial and fungal strains can colonize epoxy polymers, enzymes capable of efficiently degrading these materials have not yet been reported. Consequently, there is an urgent need for an effective, sustainable, and biologically inspired solution for CFRP recycling. Here, a chemo-enzymatic two-step oxidation process was developed. A chemical pre-treatment with propionic acid and hydrogen peroxide was used to recover imbedded carbon fibers. Additionally, three novel bacterial laccases isolated from a European spruce bark beetle gut metagenome (Ips typographus) demonstrated the ability to oxidize three epoxy resin scaffolds derived from TGMDA-based epoxy resin system, a high-performance material commonly used in aerospace applications. The sequential combination of both oxidative steps enabled the retrieval of clean carbon fibers and showed the potential of the laccase to partially further modify the pre-treated cured epoxy. This bio-inspired approach marks an initial step toward developing a bio-based recycling method for epoxy CFRPs.